Confronting Challenges in Islamic Studies (American Journal of Islam and Society, 2017)
At the 2016 meeting of the American Academy of Religion in San Antonio,the International Institute of Islamic Thought (IIIT) hosted the third annualIsmail al Faruqi Memorial Lecture. Delivered by Ahmad Atef Ahmad (Universityof California Santa Barbara), the lecture focused on the changing academicfield of Islamic studies: where the field has been, where it is now, andwhere it should go in the future.Ahmad began by outlining the history of approaching both Islamic studiesand comparative religion in general. After decades of claiming neutrality, hebelieves that the field has now reached a new phase. “In the past there was anassumption that there is a neutral, global set of rules and tools that can help usunderstand religion, like those of philosophy or anthropology. However, overtime we have come to realize that these tools are in no way neutral and comewith their own kinds of baggage.” This failure of neutrality has particularlyaffected scholars of Islam, because “You find that Muslim scholars who taketheir primary sources seriously find the deck stacked against them, especiallyfor those who are working in the West and trying to engage in conversationswith other religious traditions.”As a result of the realization that the tools of religious studies cannot beneutral, academia has undergone a significant shift ...